Kejujuran sebagai Kearifan Lokal di SMKN 1 Wonosari - Thoriq Nurmadiansyah (UIN Sunan Kalijaga Yogyakarta, 2012)
This article discusses the development of local wisdom SMKN 1 Wonosari. Local Wisdom are closely related to honesty was initiated in order to strengthen the nation's character. The study was conducted in the cafeteria honesty SMKN 1 Wonosari.